Cerebral microdialysis - Mahajan, Charu; Rath, Girija P (Journal of Neuroanaesthesiology and Critical Care, 2015)
Cerebral microdialysis is one of the latest neuromonitoring modalities introduced to clinical practice. It is a bedside monitor used to assess brain tissue biochemistry. The principle of this technique is closely related to brain metabolism and dialysis. Microdialysis helps monitoring different metabolites related to energy and metabolic cascades (glucose, lactate and pyruvate), amino acids (glutamate) and markers of cell membrane degradation (glycerol). Its role has been established in conditions such as traumatic brain injury, subarachnoid haemorrhage, ischaemic stroke, etc. However, it is yet to be included in routine neuromonitoring as the technique is very expensive, needs technical expertise and the measurement is not continuous with a lag period in-between two readings. Till date, it is mostly used as a research tool, even though it is a very promising technique in certain clinical conditions.
Keywords: Brain metabolism; cerebral microdialysis; multimodal monitoring; subarachnoid haemorrhage; traumatic brain injury